Export-led growth hypothesis: an empirical evidence of Malaysia - Abdullah, Ahmad Zainuddin (Penerbit Universiti Kebangsaan Malaysia, 1993)
This paper empirically investigates export-led growth hypothesis in total Malaysian exports and exports to dynamic Asia-Pacific and non-Asia Pacific countries by using a three-variable vector autoregressive (VAR) model. The model was subjected to three different causality test procedures; Granger's causality, Hsiao's technique and variance decomposition. The results indicate that export-led growth hypothesis is supported in two out of three series used and exports to Asia-Pacific counties have helped Malaysia to enjoy a high growth rate.